Archaeology and places of memories in the Peruvian Andes: a diachronic vision from architecture - Guzmán Juárez, Miguel (2023)
Here we explore the pathways and views conceived about the places of memories in the Peruvian Andes, where different social groups materialized feelings, knowledge, and temporal urgencies through ritual actions, spatial organizations and symbols in the recreated landscape. The sacredness of the spaces take on a particular dimension in the paths and transformations since precolonial times, where ancestry and the words, concepts, and thought systems acquire renew validity until present times. This is a diachronic analysis of the spatial experiences that took place and are held in buildings, settlements, and territories on the basis of specific and relevant cases. We argue that architecture, from its different fields – spatial, temporal and social –, articulate configurations, images, and experiences that constitute the foundations for creating complex spaces of memory, in sync with everyday life, subalternity, and otherness.